1989
DOI: 10.1002/jbm.820230503
|View full text |Cite
|
Sign up to set email alerts
|

The bovine pericardial xenograft: II. Effect of tethering or pressurization during fixation on the tensile viscoelastic properties of bovine pericardium

Abstract: Our previous article suggested that control of the extensibility of aldehyde-fixed pericardium could be achieved by controlling shrinkage during fixation. Therefore, to prevent shrinkage, we have used sandpaper-lined plexiglass plates to clamp circular samples of bovine pericardium during fixation in glutaraldehyde, tethering them at their original dimensions. As well, we have applied transmural pressures of 50 or 100 mm Hg during fixation using a hydraulic column of glutaraldehyde solution. Strips cut at 0 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Further, six of the 13 fibrils showed linear behaviour. At the tissue level, our findings are also consistent with the findings of Lee et al [65][66][67], who found no change in MTM in cross-linked pericardial tissues as in our study (table 2). It is interesting to note that, when using the native tissue fibre-ensemble model (equation (4.4)) on both the native and cross-linked data (figure 5), one can increase the fibre modulus determined from the native state to match the post-EXL data (figure 11a).…”
Section: Major Findingssupporting
confidence: 93%
“…Further, six of the 13 fibrils showed linear behaviour. At the tissue level, our findings are also consistent with the findings of Lee et al [65][66][67], who found no change in MTM in cross-linked pericardial tissues as in our study (table 2). It is interesting to note that, when using the native tissue fibre-ensemble model (equation (4.4)) on both the native and cross-linked data (figure 5), one can increase the fibre modulus determined from the native state to match the post-EXL data (figure 11a).…”
Section: Major Findingssupporting
confidence: 93%